A multidisciplinary approach to rescue a full-term pregnant and her fetus after blunt abdominal trauma: A case report and literature review - Ismail Mahmood (14150352) (2022)
Blunt abdominal trauma due to motor vehicle crash is one of the leading causes of mortality during pregnancy. Though the trauma team plays a critical role in the initial management, a multidisciplinary contribution is essential to ensure the safety of the mother and her fetus. This case report followed the multidisciplinary approach for the management of a 32-year-old female during the last week of pregnancy. She sustained blunt trauma causing maternal and fetal distress due to abruption of the placenta with a large intrauterine and retroplacental hemorrhage, retro-hepatic and retroperitoneal hemorrhage, pseudoaneurysm of uterine arteries leading to postpartum hemorrhage. Immediate intervention and management at a Level 1 trauma center led to survival of both the mother and infant.  Other information Published in: Journal of Surgical Case Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1093/jscr/rjac559